On the identity of Sium frigidum (Apiaceae) - Wang, Lisong; Zhang, Hongrui; Watson, Mark F.; Knapp, Sandra (Phytotaxa, 2016)
Taxonomic identity of Sium frigidum remains confusing; the taxon has been treated as belonging to four different genera including Apium, Sium, Chamaesium and Sinocarum. After field investigation, detailed examination of herbarium specimens, and analyses of molecular data, the results show that S. frigidum represent plants only known from southwest China, and conspecific with Apium ventricosum. Therefore, a new combination name, Sium ventricosum, is proposed with full taxonomic treatments. Taxonomic confusing related with this species is also discussed.